A Case of Contested Cremains Analyzed Through Metric and Chemical Comparison1. Issue 4 (5th March 2015) - Bartelink, Eric J.; Sholts, Sabrina B.; Milligan, Colleen F.; Van Deest, Traci L.; Wärmländer, Sebastian K.T.S.
Abstract Since the 1980s, cremation has become the fastest growing area of the U.S. funeral industry. At the same time, the number of litigations against funeral homes and cremation facilities has increased. Forensic anthropologists are often asked to determine whether the contents of an urn are actually cremated bone, and to address questions regarding the identity of the remains. This study uses both metric and chemical analyses for resolving a case of contested cremains. A cremains weight of 2021.8 g was predicted based on the decedent's reported stature and weight. However, the urn contents weighed 4173.5 g. The urn contents also contained material inconsistent with cremains (e.g., moist sediment, stones, ferrous metal). Analysis using XRD and SEM demonstrated that the urn contained thermally altered bone as well as inorganic material consistent with glass fiber cement. Although forensically challenging, cremains cases such as this one can be resolved using a multidisciplinary approach.